Studi Komparatif Kualitas Komunikasi pada Pasangan Long Distance Marriage (LDM) dan Non-LDM Perspektif Interaksi Simbolik - Saadah, Mazroatus; Sulthon, M. (STAINI Press, 2025)
Communication serves as a vital foundation in maintaining marital harmony, especially for couples in Long Distance Marriage (LDM) and those who are not. This study aims to analyze communication quality in both types of couples from the perspective of symbolic interactionism theory. This theory emphasizes that meaning is constructed through interaction, which is crucial for understanding relationship dynamics. The research employs a qualitative approach, conducting in-depth interviews with LDM and non-LDM couples. Findings reveal that LDM couples rely on digital technology to create communication symbols, such as video calls and text messages, as mediums of affection and emotional support. However, physical distance often challenges the full grasp of their interaction's meaning. In contrast, non-LDM couples benefit from direct physical presence, enriching the non-verbal dimension of their communication, yet are not free from potential conflicts due to high interaction intensity. This study concludes that communication quality is influenced not only by interaction intensity but also by the couples' ability to create and interpret relevant symbols within their relational dynamics.